Directly adaptive control for robotic manipulators with time varying uncertainties - Hoang Duy; Do Manh Dung; Nguyen Hoai Nam; Nguyen Doan Phuoc (Journal of Military Science and Technology, 2022)
The paper proposes an approach of directly adaptive control for manipulators, which is applicable to control the robotics perturbed by time varying uncertain parameters. This approach is established based on combining the well known conventional feedback linearization method and the here in this article proposed model based online observation of uncertainties. The tracking control performance of this proposed directly adaptive controller has been verified peer theoretical method and numerical simulation.